Exploring the Intersection of Brands and Linguistics: A Comprehensive Bibliometric Study - Lukose, Alan; Cleetus, Regina Sibi; Divya, H.; Saravanakumar, T. M.; Jose, Jobin (International Review of Management and Marketing, 2024)
Branding has emerged as a multidiscipline with complication, conveyed by integrated digital technologies, AI, and rich linguistic approaches. This paper depicts the research landscape at the juncture of branding and linguistics, supported by VOSviewer, Biblioshiny, and CiteSpace in pinpointing key trends, themes, and collaboration networks. Drawing on data collected from Scopus, this study investigates the shifts in traditional branding strategies caused by technologies of machine learning, sentiment analysis, and social media platforms. It highlights the contributions made by leading authors, major publication sources, and patterns of international collaboration in influential works. Finally, thematic and co-occurrence analysis shows significant movement into data-based and computational approaches. This also points out some research gaps in the field of digital branding’s long- term effects, ethical considerations of AI-photo strategies, and multilingual branding approaches that provide a useful basis for future research and practical application innovation in the field of branding.